Active Disturbance Rejection Control of Thermal Power Unit Coordinated System based on Frequency Domain Analysis - Ruiqing Zhang; Liangyu Ma; Yongguang Ma; Yang Liang; Liwei Geng (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
For the multi-input and multi-output, strong-coupling nonlinear features of coordinated system for thermal power unit, it is difficult for traditional PID coordinated control scheme to meet the power grid demand which often participates in peak regulation and frequency modulation. In this paper, Inverse Nyquist array is employed to carry out frequency domain analysis of the plant model. Then Pseudo diagonalization is used to design the static decoupling compensation matrix of the system. Above on these, the linear active disturbance rejection controller of every channel in coordinated system can be designed repectively. Dynamic coupling and system unknown parts are observed by extended state observer of ADRC and is compensated to the system in time. The simulation tests show that the disturbance rejection results of the load and the main steam pressure for the coordinated control system under LADRC is better than that of PID control.